2013
DOI: 10.1590/s0102-695x2012005000136
|View full text |Cite
|
Sign up to set email alerts
|

Citotoxic activity evaluation of essential oils and nanoemulsions of Drimys angustifolia and D. brasiliensis on human glioblastoma (U-138 MG) and human bladder carcinoma (T24) cell lines in vitro

Abstract: The species Drimys angustifolia Miers and D. brasiliensis Miers, commonly known as "casca-de-anta", have in their leaves essential oils that can confer cytotoxic effects. In this study, we evaluated the citotoxic effects of the volatile oils from these two species. We also proposed a nanoemulsion formulation for each of the species and assessed the in vitro cytotoxicity on U-138 MG (human glioblastoma) and T24 (human bladder carcinoma) cell lines. The plant chemical composition was evaluated by gas chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…The NE of both oils were not active on the U-138 MG, but had significant cytotoxicity effects towards the T24 lineage. Then, this study found that, these encapsulated oils showed a significant improvement in cytotoxic activity against tumor cells compared to their pure form (Gomes et al, 2013).…”
Section: Pitmentioning
confidence: 92%
See 2 more Smart Citations
“…The NE of both oils were not active on the U-138 MG, but had significant cytotoxicity effects towards the T24 lineage. Then, this study found that, these encapsulated oils showed a significant improvement in cytotoxic activity against tumor cells compared to their pure form (Gomes et al, 2013).…”
Section: Pitmentioning
confidence: 92%
“…In vitro antiparasitic activity (Baldissera et al, 2013) Anise (25, 50 and 75% of oil phase) Soy lecithin (5%) HPH In vitro antimicrobial activities (Topuz et al, 2016) Argan Polyethoxylated solutol HS-15 EPI In vitro cytotoxic activity (Jordan et al, 2012) Babassu (5%) Mixture of sorbitan monooleate and PEG-54 castor oil (10%) PIT Pharmaceutical and cosmetic matrices (Gumiero, Filho,2012) Carqueja-doce (3.32%) Polysorbate (0.77%) SE In vitro antifungal activity (Danielli et al, 2013) Casca-de-anta (4%) Polysorbate 20 (1%) Sorbitan monooleate (1%) HPH In vitro cytotoxic activity (Gomes et al, 2013) Cinnamon (6%) Polysorbate 80 (18%) EPI In vitro antibacterial activity (Nirmala et al, 2013) Cinnamon bark (1%)…”
Section: Hphmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Limberger et al (2007), studying the essential oils from the species, noted that the yields ranged from 1.4 to 1.5% for the oils from fresh leaves, 1.0% for the oils from dry leaves, 0.4 to 0.6% for the oils from stem barks and 0.4% for the oils from unripe fruits. Gomes et al (2013) found, for the same species, a yield of approximately 0.3% for the oil from fresh leaves.…”
Section: Resultsmentioning
confidence: 74%
“…In this study, the phenylpropanoids identified were safrole, eugenol, methyl eugenol, myristicin and 2,6- dimethoxy-4-allylphenol (Table 6). Except for 2,6dimethoxy-4-allylphenol, all these compounds have already been found in the essential oils from D. brasiliensis (Limberger et al 2007;Ribeiro et al 2008;Lago et al 2010;Gomes et al 2013).…”
Section: Chemical Composition Of the Essential Oilsmentioning
confidence: 99%